A Flexible Solid Electrolyte Interphase Layer for Long‐Life Lithium Metal Anodes - Li, Nian‐Wu; Shi, Yang; Yin, Ya‐Xia; Zeng, Xian‐Xiang; Li, Jin‐Yi; Li, Cong‐Ju; Wan, Li‐Jun; Wen, Rui; Guo, Yu‐Guo (Angewandte Chemie International Edition, 2018)
Lithium (Li) metal is a promising anode material for high‐energy density batteries. However, the unstable and static solid electrolyte interphase (SEI) can be destroyed by the dynamic Li plating/stripping behavior on the Li anode surface, leading to side reactions and Li dendrites growth. Herein, we design a smart Li polyacrylic acid (LiPAA) SEI layer high elasticity to address the dynamic Li plating/stripping processes by self‐adapting interface regulation, which is demonstrated by in situ AFM. With the high binding ability and excellent stability of the LiPAA polymer, the smart SEI can significantly reduce the side reactions and improve battery safety markedly. Stable cycling of 700 h is achieved in the LiPAA‐Li/LiPAA‐Li symmetrical cell. The innovative strategy of self‐adapting SEI design is broadly applicable, providing opportunities for use in Li metal anodes Stretching exercises: A flexible lithium polyacrylic acid (LiPAA) solid electrolyte interphase (SEI) layer which is highly stretchable is designed to address the dynamic volume changes during Li plating/stripping on the Li anode surface in Li ion batteries. The LiPAA polymer SEI can significantly reduce the side reactions and improve the safety performance.